The social embeddedness of transactions: Evidence from the residential real estate industry - Sawyer, Steve; Kevin Crowston; Rolf Wigand; Allbritton, Marcel (The Information Society, 2003)
Information and communications technologies (ICT) are becoming pervasive in the residential real-estate industry and their usage is affecting the work lives of real-estate agents. Drawing on data from a regional study of the residential real-estate industry in the United States, we focus on the disintermediation or, more accurately, the reintermediation of real-estate agents in the sales process. Using data collected from interviews, direct observation, and archival records, we examine how real-estate agents are (1) taking advantage of new ICT in their work, and (2) protecting themselves from others wishing to displace their position in the real-estate value chain. Our analysis of this activity draws on two contrasting theoretical perspectives to illuminate the roles of residential real-estate agents: transaction cost and social capital. The results of this study provide insights into the ways in which ICT are used to build and draw on the social relationships that underpin the actual transactions, to help guide the process of buying/selling a house, and to invoke expertise as needed.
Keywords: Computer-Mediated Communication; Coordination; Real Estate